2014
DOI: 10.1007/s10815-014-0293-1
|View full text |Cite
|
Sign up to set email alerts
|

Polar body based aneuploidy screening is poorly predictive of embryo ploidy and reproductive potential

Abstract: PurposePolar body (polar body) biopsy represents one possible solution to performing comprehensive chromosome screening (CCS). This study adds to what is known about the predictive value of polar body based testing for the genetic status of the resulting embryo, but more importantly, provides the first evaluation of the predictive value for actual clinical outcomes after embryo transfer.MethodsSNP array was performed on first polar body, second polar body, and either a blastomere or trophectoderm biopsy, or th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 28 publications
(51 reference statements)
0
17
1
Order By: Relevance
“…Intriguingly, they also found a higher contribution of metaphase II errors to embryo aneuploidy than previously reported. Some oocytes with aneuploid PBs, however, can go on to produce euploid embryos (56,61). The mechanism underlying this self-correction mechanism is not understood, but the ability of nondisjunction occurring during meiosis to correct during later preimplantation development reduces the specificity of PGS in PBs.…”
Section: Aneuploidy Screening In Pbsmentioning
confidence: 99%
“…Intriguingly, they also found a higher contribution of metaphase II errors to embryo aneuploidy than previously reported. Some oocytes with aneuploid PBs, however, can go on to produce euploid embryos (56,61). The mechanism underlying this self-correction mechanism is not understood, but the ability of nondisjunction occurring during meiosis to correct during later preimplantation development reduces the specificity of PGS in PBs.…”
Section: Aneuploidy Screening In Pbsmentioning
confidence: 99%
“…This would suggest that the error arose during mitosis and not meiosis. Previous research has demonstrated that ∼ 25% of polar bodies are aneuploid [Salvaggio et al, 2014], while ∼ 50% of blastocysts are aneuploid [Taylor et al, 2014b, c]. The higher incidence of aneuploidy at the blastocyst stage suggests that a majority of aneuploidy may be mitotic in origin.…”
Section: Discussionmentioning
confidence: 99%
“…1 Although polar body biopsy is less invasive, it is less predictive of actual clinical outcome than direct embryo assessment. 2 Genetic laboratories have developed their own protocols to perform different molecular tests on the limited amount of DNA obtained from biopsy. Traditionally, fluorescent in-situ hybridisation is used for cytogenetic diagnosis, and polymerase chain reaction for molecular diagnosis.…”
Section: Recent Advances In Preimplantation Genetic Diagnosismentioning
confidence: 99%